2016
DOI: 10.1590/2359-3997000000136
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the left ventricular function in normotensive prediabetics: a tissue Doppler echocardiography study

Abstract: Objective: Several studies have shown that left ventricular (LV) dysfunction is increased in individuals with diabetes. However, there are scarce data about LV function in prediabetics. This study assessed the early changes in LV diastolic and systolic myocardial function in normotensive prediabetics using tissue Doppler echocardiography (TDE). Subjects and methods: We evaluated 94 patients with prediabetes (mean age of 50.8 ± 6.9 years, 78 female) without known cardiovascular diseases and 70 healthy volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 35 publications
3
15
1
Order By: Relevance
“…(8) We have also found that total cholesterol, triglycerides, LDL and VLDL were significantly higher in prediabetes and high density lipoprotein were significantly lower in prediabetes as compared to controls (p=0.0001). Same observation was seen by Murat Akçay et al (8) Myocardial performance index in cases was higher than controls. Difference in MPI in cases and controls was found to be statistically significant.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…(8) We have also found that total cholesterol, triglycerides, LDL and VLDL were significantly higher in prediabetes and high density lipoprotein were significantly lower in prediabetes as compared to controls (p=0.0001). Same observation was seen by Murat Akçay et al (8) Myocardial performance index in cases was higher than controls. Difference in MPI in cases and controls was found to be statistically significant.…”
Section: Discussionsupporting
confidence: 53%
“…(p<0.05, S) Similarly, Murat Akçay et al reported BMI was statistically higher in prediabetes in comparison to age and sex matched controls. (8) In our study waist hip ratio was higher in prediabetes when compared to age and sex matched controls. However, Murat Akçay et al reported that mean waist hip ratio for cases and controls were almost similar.…”
Section: Discussionsupporting
confidence: 47%
“…Ayalon et al 1 reported that preclinical left ventricle diastolic dysfunction could occur independently of left ventricle hypertrophy in metabolic syndrome with lower E/A ratio and mean e′. While Tadic et al 27 found non-dipping pattern and metabolic syndrome separately cause left ventricle diastolic dysfunction in hypertensive patients, Akçay et al 28 found lower E/A ratio, higher E/e′ and myocardial performance index values in normotensive prediabetics. Furthermore, Karakurt et al 26 found that adult metabolic syndrome patients with preserved left ventricle ejection fraction had low E, E/A ratio in right ventricle, and high right ventricle global myocardial performance index as compared to the control group and identified diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…One study detected no difference concerning these variables between Pre‐DM subgroups and cases with DM. The available results are contradictory in that whereas some studies have found differences with respect to the aforementioned variables between some Pre‐DM subgroups and NL groups, some other investigations have reported no difference 15,17,24,25,29 . Two studies compared Pre‐DM subgroups (HbA1c < 5.7% vs HbA1c = 5.7%‐6.4%) with each other and revealed no difference regarding TDI‐based velocities 39,44 and LV longitudinal deformations 44 .…”
Section: Resultsmentioning
confidence: 93%